Neuroimmune Interactions and Rhythmic Regulation of Innate Lymphoid Cells - Jacquelot, Nicolas; Belz, Gabrielle T.; Seillet, Cyril (Frontiers in Neuroscience, 2021)
The Earth’s rotation around its axis, is one of the parameters that never changed since life emerged. Therefore, most of the organisms from the cyanobacteria to humans have conserved natural oscillations to regulate their physiology. These daily oscillations define the circadian rhythms that set the biological clock for almost all physiological processes of an organism. They allow the organisms to anticipate and respond behaviorally and physiologically to changes imposed by the day/night cycle. As other physiological systems, the immune system is also regulated by circadian rhythms and while diurnal variation in host immune responses to lethal infection have been observed for many decades, the underlying mechanisms that affect immune function and health have only just started to emerge. These oscillations are generated by the central clock in our brain, but neuroendocrine signals allow the synchronization of the clocks in peripheral tissues. In this review, we discuss how the neuroimmune interactions create a rhythmic activity of the innate lymphoid cells. We highlight how the disruption of these rhythmic regulations of immune cells can disturb homeostasis and lead to the development of chronic inflammation in murine models.